Syringoma of vulva: an unusual presentation. Clinical, morphological and immunohistochemnical aspects. - Núñez, José; Viloria, María (Investigación Clínica, 2015)
The case of a 34-year-old woman, who consulted because she observed the appearance of numerous yellow-white asymptomatic papules on the vulva, is presented. Clinical diagnosis of syringoma of vulva was established. The pathological and immunohistochemical studies confirmed the diagnosis. Vulvar syringoma usually occurs as a multiple flesh-colored or brownish papules on both sides of labia majora of women in their third decade. Its diagnosis should be considered when the patient complaints of vulvar pruritus and/or sweating.